Analysis of influence of materialism on impulsive buying and compulsive buying with credit card use as mediation variable - Cuandra, Fendy; Kelvin, Kelvin (JURNAL MANAJEMEN, 2021)
Having unlimited needs and wants, humans as economic beings will struggle to meet their needs. In this modern era, shopping for human needs and desires has become easier to do with the availability of various stores and malls to online retail. This ease of shopping has increased interest in shopping for unlimited material needs and indulges Indonesians to continue making purchases in order to develop uncontrolled compulsive buying behavior. Therefore the authors aim to examine the effect of materialism on compulsive buying mediated by the use of credit cards and impulsive buying. The object of this research is credit card users in Batam. Sampling was done by giving a google form questionnaire to credit card users in the city of Batam. Demographic data of respondents were then analyzed using IBM SPSS Statistics version 25.0 and analysis of the effect of independent variables on the dependent variable was carried out using Smart PLS version 3.2.8. The results of this study indicate that the variables of materialism, use of credit cards and impulsive buying have a significant effect on compulsive buying.